Pengaruh Influencer Marketing dan Product Knowledge Terhadap Minat Beli Product Skincare Ms Glow di Kota Bima - ST Rahmah; Ismunandar Ismunandar; Sri Ernawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyze the influence of influencer marketing and product knowledge on the buying interest of Ms Glow skincare products in Bima City. The research method used is a survey with a quantitative approach. Data was collected through a questionnaire distributed to 200 respondents who were potential users of Ms Glow products. Data analysis was carried out using multiple linear regression. The results of the study show that influencer marketing has a significant influence on buying interest, which is characterized by the power of social media in building consumer trust. In addition, product knowledge has also proven to play an important role in increasing buying interest, where consumers who better understand the benefits and uses of the product tend to be more interested in buying. The conclusion of this study is that a marketing strategy through influencers and good product education can increase consumer buying interest in Ms Glow skincare products in Bima City.